Cytogenetics of Stump-tailed Macaque, Macaca arctoides (Primate, Cercopithecidae) in Thailand by Conventional Staining - TANOMTONG, Alongkoad; KHUNSOOK, Sumpars; KAENSA, Wiwat; KONGKHAM, Wichit (Walailak Journal of Science and Technology (WJST), 2011)
The cytogenetics of the stump-tailed macaque (Macaca arctoides) in Thailand was studied. Blood samples were collected from this species maintained in Nakhon Ratchasima Zoo and Songkhla Zoo. After standard whole blood lymphocytes were cultured in the presence of colchicine, metaphase cells were spreaded on the slide and air-aired. Chromosomes were observed using Conventional Giemsa staining under a light microscope. The results show that the number of diploid chromosomes of the stump-tailed macaque is 2n=42, and the fundamental number (NF) are 84 chromosomes in the female and male. The types of autosomes are 6 large metacentric, 8 large submetacentric, 4 medium metacentric, 12 medium submetacentric, 8 small metacentric and 2 small submetacentric chromosomes. In addition, the pair of chromosome 13 is a clearly observable satellite chromosome. The X chromosome is medium submetacentric and the Y chromosome is the smallest submetacentric chromosome.